Long-Term Suffering from Respiratory Tract Infections and Its Impact on Quality of Life: A Cross-Sectional Study - Wattimena, Christy; Sasarari, Zusana A.; Herman, Theresie Chindyana; Kristina, Yunita (Sekolah Tinggi Ilmu Kesehatan Stella Maris Makassar, 2025)
Acute Respiratory Infections (ARI) are infectious diseases that attack the acute respiratory tract, including the nose, throat, and lungs. The purpose of the research to determine the relationship between the duration of ARI and the quality of life. The study was conducted at the Waibhu Community Health Centre using non-probability sampling with purposive sampling techniques. The sample size was 80 with inclusion criteria of ARI patients aged 19-60 years; duration of ARI are 5-30 days; fully conscious; able to read and write; and willing to be respondents. Respondents who experienced disorientation in time, place, and person were excluded. The instrument used the WHOQOL-BREFF questionnaire to measure quality of life. Data analysis used univariate analysis (gender, age, occupation, marital status, religion, duration of ARI, number of ARI episodes in the last 6 months, and quality of life) and bivariate analysis (the relationship between the duration of ARI and the quality of life) used the Kruskal-Wallis test. The results showed that there was a significant relationship between the duration of ARI and the quality of life of ARI patients (p=0.001), H=16.336. It is necessary to pay attention to the patient's quality of life to preventing the severity of infection.